Phenformin suppresses angiogenesis through the regulation of exosomal microRNA-1246 and microRNA-205 levels derived from oral squamous cell carcinoma cells - Zhuang, Dexuan; Wang, Shuangshuang; Liu, Guanyi; Liu, Panpan; Deng, Huiting; Sun, Jianfeng; Liu, Chang; Leng, Xue; Zhang, Qun; Bai, Fuxiang; Mi, Jun; Wu, Xunwei (Frontiers in Oncology, 2022)
Exosomes secreted by cancer cells are important components in the tumor microenvironment, enabling cancer cells to communicate with each other and with noncancerous cells to play important roles in tumor progression and metastasis. Phenformin, a biguanide antidiabetic drug, has been reported to have a strong antitumor function in multiple types of cancer cells, however little research has been reported about whether phenformin can regulate the secretion of exosomes by cancer cells to regulate the tumor microenvironment and contribute to its antitumor function. Here we found that exosomes (Phen-Exo) derived from phenformin-treated oral squamous cell carcinoma (OSCC) cells significantly suppress the proliferation, migration and tube formation of human umbilical vein endothelial cells (HUVECs) in vitro. The inhibition of angiogenesis by Phen-Exo was verified in vivo by matrigel plug angiogenesis assays and by chick chorioallantoic membrane assays. Mechanistically, we discovered that the expression of microRNA-1246 (miR-1246) and microRNA-205 (miR-205) was significantly increased in exosomes secreted by OSCC cells treated with phenformin, while high expression levels of miR-1246 or miR-205 in vascular endothelial cells inhibited their angiogenic effects and decreased expression of the angiogenic factor VEGFA. In conclusion, these results reveal that phenformin can inhibit angiogenesis by regulating the levels of miR-1246 and miR-205 in exosomes secreted by OSCC cells, suggesting that phenformin has the potential to alter the tumor microenvironment to antagonize the growth of OSCCs, which provides a theoretical basis for developing new strategies to treat OSCCs in the future.